Pelestarian Lokomotif Uap Silukah di Kabupaten Sijunjung: Evaluasi dalam Kerangka Cultural Heritage Management - Ivo Giovanni; Mentari Halimun; Isman Pratama Nasution (Penerbit BRIN (BRIN Publishing), 2026)
Abstract. Preservation of The Silukah Steam Locomotive in Sijunjung Regency: Evaluation Within the Framework of Cultural Heritage Management. The Silukah Steam Locomotive is a remnant of the Muaro Sijunjung–Pekanbaru railway construction during the Japanese occupation, closely associated with memories of forced labor involving romusha and prisoners of war. As a cultural heritage asset with significant historical, social, and humanitarian values, it faces challenges related to material deterioration, limited planning, and low community involvement in management processes. This study aims to evaluate the preservation of the Silukah Steam Locomotive within the framework of Cultural Heritage Management by positioning preservation as part of broader heritage management strategies. The research employs a qualitative approach through direct observation of conservation activities and a literature review on cultural heritage management. Data were qualitatively analyzed to examine patterns of community participation, management challenges, and opportunities for sustainable development. The results indicate that preservation efforts have included inventory, heritage designation, and physical conservation involving local labor; however, community participation remains largely confined to technical roles. This study recommends the development of a values-based management plan, the strengthening of community roles in strategic decision-making, and the integration of educational use supported by appropriate institutional frameworks. Keywords: Silukah Steam Locomotive, Cultural heritage management, Conservation, Community- based management Abstrak. Lokomotif Uap Silukah merupakan tinggalan pembangunan jalur kereta api Muaro Sijunjung–Pekanbaru pada masa pendudukan Jepang yang sarat memori penderitaan akibat kerja paksa romusha dan tawanan perang. Sebagai warisan budaya dengan nilai historis, sosial, dan kemanusiaan yang tinggi, lokomotif ini menghadapi tantangan degradasi material, keterbatasan perencanaan, serta rendahnya keterlibatan masyarakat dalam pengelolaan. Penelitian ini bertujuan mengevaluasi pelestarian Lokomotif Uap Silukah dalam kerangka Cultural Heritage Management dengan menempatkan pelestarian sebagai bagian dari strategi pengelolaan warisan budaya yang lebih luas. Penelitian menggunakan pendekatan kualitatif melalui observasi langsung pada kegiatan konservasi dan studi literatur terkait pengelolaan cagar budaya. Data dianalisis secara kualitatif untuk mengidentifikasi dinamika pelibatan masyarakat, tantangan pengelolaan, serta peluang pengembangan berkelanjutan. Hasil penelitian menunjukkan bahwa upaya pelestarian telah dilakukan melalui inventarisasi, penetapan cagar budaya, dan konservasi fisik dengan melibatkan tenaga lokal, namun partisipasi masyarakat masih terbatas pada aspek teknis. Penelitian ini merekomendasikan penyusunan rencana pengelolaan berbasis nilai, penguatan peran komunitas dalam pengambilan keputusan, serta integrasi pemanfaatan edukatif dan dukungan kelembagaan. Kata kunci: Lokomotif Uap Silukah, Pengelolaan cagar budaya, Konservasi, Pengelolaan berbasis komunitas